An Experimental Study to Evaluate the Anti-Microbial Effect of Fumigation with Sarshapanimbadi Dhoopa (International Journal of Ayurveda and Pharma Research, 2025)
Nowadays rising airborne diseases are one of the major health concerns of the entire world. Prevalence of various respiratory diseases are increasing in persons exposing to contaminated environment. Therefore, disinfection of our environment is most important. In Ayurveda, Dhoopana is a method of disinfection. Sarshapanimbadidhoopa mentioned in Sushruta Samhita with ingredients Sarshapa, Nimba, Saindhava and Ghrita was selected for the study to evaluate its antimicrobial activity. Primarily Staphylococcus aureus and Candida albicans were identified from different treatment procedure rooms of hospital by placing petri dishes open for one hour with suitable medium. Fumigation of identified microbes were done within a glass chamber with and without adding Dhoopanadravya to red hot charcoal. In addition to that one set of microbial plate of bacteria and fungus were kept as such without fumigation for the assessment of efficacy of fumigation. Fumigation was done with varying doses (15g, 20g, 25g and 30g) and time span (5minutes, 10minutes, 15minutes and 20minutes). Results obtained were statistically analyzed using independent t-test, ANOVA test and paired t-test. Reduction in Colony Forming Unit (CFU) of bacteria and fungi were found to be significant and fumigation with adding Dhoopachoorna was found to be more significant than without adding Dhoopachoorna to charcoal. Complete cessation of bacterial CFU was found on fumigation with 30g Choorna for 20minutes and fungal CFU was found on fumigation of 25g Choorna for 15minutes. The study concluded that Sarshapanimbadi Dhoopa has antimicrobial effect.